Fuel cell technology for sustainable development in Pakistan – An over-view. (January 2016) - Raza, Rizwan; Akram, Nadeem; Javed, Muhammad Sufyan; Rafique, Asia; Ullah, Kaleem; Ali, Amjad; Saleem, M.; Ahmed, Riaz
Abstract: Fuel cell technology holds the combination of benefits, which are barely offered by any other energy generating technology. Because the fuel used in this technology is found in abundance in nature and can also be renewed/sustained. Pakistan is blessed with renewable energy resources which are suitable for fuel cell technology. Therefore, fuel cell technology offers a great opportunity to meet the demand of energy and for the sustainable development of Pakistan. The energy research group at COMSATS Institute of Information Technology (CIIT), Lahore has made efforts to study the technical aspects of fuel cell technology and its commercial benefits. The research group is interested in finding ways and means of generating and storing the energy produced by using fuel cells. In this paper, the research activities on fuel cell technology in Pakistan have been reviewed and it is also discussed how this technology can resolve the current energy crises in Pakistan and can be the source of sustainable energy. It has been also reviewed that the country would greatly benefit from fuel cells and fuel cell hybrid system (environmental friendly technology), which could be the best solution for electricity production as well for automobile industry.